Identification and characterization of endophytic fungi from garcinia atroviridis for potential antagonistic against phytopathogenic, colletotrichum - Nur Afeeqah Mohamed Zanudin,; Nor’aishah Hasan,; Patayah Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Biological control is referred to as the “use of natural or modified organisms, genes” to minimize the effects of undesirable pests, pathogenic microorganisms, and diseases on plant crops. This measure has become a suitable and safe alternative for chemical fungicides in plant disease management. Endophytic fungi have received much attention as biological control agents against many plant pathogens through antibiosis, parasitism, invading spores, mycelium, and cells of the pathogen, and secreting bioactive metabolites. While the therapeutic properties of Garcinia atroviridis have been studied, the existence of microbial endophytes and their properties is still less documented. In this research, G. atroviridis endophytic fungi were isolated and identified by fungal colony morphology observation combined with the PCR-amplified fungal internal transcribed spacer (ITS) sequence analyses. Fungal endophytes were assessed for their biocontrol potential against Colletotrichum gloeosporioides. In total, 111 endophytic fungal isolates harboring inside the leaf, branch, and fruit of G. atroviridis belonged to 5 different species with 3 different genera and two unidentified genera. All the endophytic fungal species isolated were evaluated using an in vitro dual culture assay against C. gloeosporioides, a common pathogen that causes anthracnose disease. The results of the present study clearly showed that seven species of isolated fungal endophytes were capable of inhibiting the mycelial colony growth of C. gloeosporioides with an inhibition percentage between 54.67% to 87.94%. Among these species, Nigrospora sphaerica recorded the highest PIRG with 87.94%. Our work indicates that endophytic fungi isolated from G. atroviridis have a biocontrol effect on C. gloeosporioides and are expected to be a potential source of bioactive metabolites.